Penyisihan Kadar Logam Fe Dan Mn Pada Air Gambut Dengan Pemanfaatan Geopolimer Dari Kaolin Sebagai Adsorben - Ade Anggriawan; Edy Saputra; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Geopolymer is kind of shyntetic compound that made by syntesizing alumino and silicate, known has similarity with zeolit. In this study eleborate that geopolymer which made by kaolin used for adsorben to remove ion Ferrum and Mangan in peat water by using adsorption process. The influence of ratio alkaline activator to kaolin and adsorbent dosage examined at constant particle size and contact time to analyzed the eficiency of removal Ferum and Mangan by using batch system. The adsorption process of geopolymer by using batch system made of kaolin as an adsorption prove that geopolymer which made by kaolin have excelence ability to removing Ferum and Mangan from peat water.Keyword: Peat water, Geopolymer, Kaolin, Ratio, Ferrum, Mangan